2016
DOI: 10.3389/fcimb.2016.00185
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of GM-CSF or CD40L Enhances the Immunogenicity of Hantaan Virus-Like Particles

Abstract: A safe and effective Hantaan virus (HTNV) vaccine is highly desirable because HTNV causes an acute and often fatal disease (hemorrhagic fever with renal syndrome, HFRS). Since the immunity of the inactivated vaccine is weak and the safety is poor, HTNV virus-like particles (VLPs) offer an attractive and safe alternative. These particles lack the viral genome but are perceived by the immune system as virus particles. We hypothesized that adding immunostimulatory signals to VLPs would enhance their efficacy. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The NP production of hantaviruses is used to quantify the amount of infectious particles and reflect the viral replication level (Koma et al, 2012 ; Barriga et al, 2013 ; Guo et al, 2015 ; Cheng et al, 2016 ; Ma et al, 2016 ). Compared with conventional methods, such as ELISA, the ICW assay promptly detected HTNV NP expression, and the results were characterized by high accuracy and quality.…”
Section: Discussionmentioning
confidence: 99%
“…The NP production of hantaviruses is used to quantify the amount of infectious particles and reflect the viral replication level (Koma et al, 2012 ; Barriga et al, 2013 ; Guo et al, 2015 ; Cheng et al, 2016 ; Ma et al, 2016 ). Compared with conventional methods, such as ELISA, the ICW assay promptly detected HTNV NP expression, and the results were characterized by high accuracy and quality.…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF has been described before as an adjuvant in DNA- or adenovirus-based immunization against HIV infection or against model antigens [35–38], in virus-like particle-based immunization against Hanta virus infection [39], and in experimental cancer immunization in pre-clinical [40] and clinical studies [41, 42]. In all of these studies, GM-CSF was reported to have an enhancing effect on CD8 + T cell responses, which it may exert indirectly by promoting the activation and maturation of dendritic cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…We found that IL1β and IL15 had only moderate effects on the induction of GagL 85–93 -specific CD8 + T cells, whereas IL2, IL12, IL21 and IL28A led to a rescue of GagL 85–93 -specific CD8 + T cell induction in most of the co-immunized mice; but clearly, GM-CSF had the most profound effect on induction of GagL 85–93 -specific CD8 + T cell responses in the presence of envelope. GM-CSF has been described before as an adjuvant in DNA- or adenovirus-based immunization against HIV infection or against model antigens [ 35 – 38 ], in virus-like particle-based immunization against Hanta virus infection [ 39 ], and in experimental cancer immunization in pre-clinical [ 40 ] and clinical studies [ 41 , 42 ]. In all of these studies, GM-CSF was reported to have an enhancing effect on CD8 + T cell responses, which it may exert indirectly by promoting the activation and maturation of dendritic cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a well-known immune-adjuvant, CD40L is widely used in DNA vaccine development (36,37). In the field of VLPs design, cd40L was successfully incorporated into Hantaan VLPs (29) and SIV VLPs, and whether it is an effective adjuvant in lung cancer VLPs based vaccine development is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cd40L/cd40 interaction serves a significant role in B-cell activation, proliferation, differentiation and antibody production (28), whereas binding of cd40L to cd40 induces the expression of costimulatory molecules that reside on antigen-presenting cells. Once these cells are activated, the cd4 + T cell responses are augmented by increased cytokine production, while the CD4 + -dependent cd8 + T cells are also activated (29). In the field of DNA vaccine design, fusion of the immune stimulatory molecule cd40L genetically was confirmed to be an effective way to obtain a robust T cell response (30).…”
Section: Incorporation Of Cd40 Ligand Enhances the Immunogenicity Of mentioning
confidence: 99%